A Latent Content Analysis of Barriers and Supports to Healthcare: Perspectives From Caregivers of Service Members and Veterans With Military-Related Traumatic Brain Injury. Issue 5 (September 2018) - Carlozzi, Noelle E.; Lange, Rael T.; French, Louis M.; Sander, Angelle M.; Freedman, Jenna; Brickell, Tracey A.
Abstract : Objective: To identify barriers and supports that caregivers of individuals with military-related traumatic brain injury (TBI) encounter when navigating the military healthcare system; this information will be used as the foundation of a new patient-reported outcome measure. Setting: Community. Participants: Forty-five caregivers of service members and veterans (SMV) who sustained a medically documented mild, moderate, severe, or penetrating TBI. Design: Latent content analysis. Main Measures: Nine focus group discussions of barriers and supports to navigating the military healthcare system and community resources. Results: Latent content analysis indicated that caregivers discussed barriers (66%) and supports (34%) to obtaining care within the military healthcare system and the community. Caregivers most frequently discussed SMVs' interactions with healthcare, their own interactions with healthcare, family care, and community organizations. Conclusions: Caregivers confront numerous challenges while pursuing healthcare services. Although much of the discussion focused on barriers and perceived unmet needs within the military healthcare system, caregivers also recognized supports within the military healthcare system and general community. Increased attention to accessibility and quality of services, as well as reducing financial burden, can lead to improved health-related quality of life for caregivers and their SMVs.